Pengaruh Komunikasi, Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan PT Telkom Pugeran Yogyakarta - Pratama, Rio Widayat; Subarjo Subarjo (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the influence of communication, compensation, and work discipline on employee performance at PT. Telkom Pugeran Yogyakarta using a quantitative approach. Primary data were collected by distributing questionnaires to 61 employees, then analyzed using a Likert scale and statistical tests through the SPSS program. The results of the study indicate that: (1) communication has a positive and significant effect on employee performance, (2) compensation has a positive and significant effect on employee performance, and (3) work discipline also has a positive and significant effect on employee performance at PT. Telkom Pugeran Yogyakarta.